1997
DOI: 10.1523/jneurosci.17-13-05206.1997
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Neurofilament Expression Selectively in Regenerating Reticulospinal Neurons

Abstract: During regeneration of lamprey spinal axons, growth cones lack filopodia and lamellipodia, contain little actin, and elongate much more slowly than do typical growth cones of embryonic neurons. Moreover, these regenerating growth cones are densely packed with neurofilaments (NFs). Therefore, after spinal hemisection the time course of changes in NF mRNA expression was correlated with the probability of regeneration for each of 18 identified pairs of reticulospinal neurons and 12 cytoarchitectonic groups of spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
176
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 114 publications
(182 citation statements)
references
References 85 publications
6
176
0
Order By: Relevance
“…Prior to surgery, lampreys were anesthetized with Finquel MS-222 (0.1 g l −1 tank water; Argent Chemical Laboratories). Spinal cord transections were performed as detailed previously (Jacobs et al, 1997;Oliphint et al, 2010). Briefly, each lamprey was placed in a Sylgard-lined Petri dish on a paper towel moistened in oxygenated lamprey Ringers (100 NaCl, 2.1 KCl, 2.6 CaCl 2 , 1.8 MgCl 2 , 4 glucose, 0.5 glutamine, 2 HEPES, pH 7.4).…”
Section: Materials and Methods Animals And Dissection Protocolmentioning
confidence: 99%
“…Prior to surgery, lampreys were anesthetized with Finquel MS-222 (0.1 g l −1 tank water; Argent Chemical Laboratories). Spinal cord transections were performed as detailed previously (Jacobs et al, 1997;Oliphint et al, 2010). Briefly, each lamprey was placed in a Sylgard-lined Petri dish on a paper towel moistened in oxygenated lamprey Ringers (100 NaCl, 2.1 KCl, 2.6 CaCl 2 , 1.8 MgCl 2 , 4 glucose, 0.5 glutamine, 2 HEPES, pH 7.4).…”
Section: Materials and Methods Animals And Dissection Protocolmentioning
confidence: 99%
“…Within a field of view, all cells within the RGC layer were scored as either unlabeled (i.e., labeled below background), weakly (labeled just above background), moderately (visible distinctly and medium blue in color), or strongly labeled (dark blue and labeled over a significant area of the cell body; Jacobs et al, 1997). These numbers were normalized against the total number of cells within the RGC layer for each field of view.…”
Section: Quantitative Shifts In the Distribution Of Nif Mrnas Among Rgcsmentioning
confidence: 99%
“…The behavior of the type IV nIFs in Xenopus regenerating optic nerve resembles that reported in successfully regenerating CNS axons in other systems. For example, in transected spinal cord axons of lamprey, NF-M expression is initially suppressed and then rises in only those axons that successfully regenerate, while remaining suppressed in those that do not (Jacobs et al, 1997). Similarly, in fish optic nerve expression of the xefiltin ortholog, gefiltin, is also initially suppressed, then rises above normal during the peak period of regeneration, and then falls to normal levels after regeneration is complete Asch et al, 1998).…”
Section: Regulation Of Type IV Nif Mrnasmentioning
confidence: 99%
“…The spinal cord of larval lampreys regenerates morphologically and functionally after transection (Rovainen, 1976;Selzer, 1978;Wood and Cohen, 1981;Jacobs et al, 1997). The growing tips of the regenerating axons have an appearance that is markedly different from the growth cones of embryonic neurons during development or in tissue culture.…”
mentioning
confidence: 99%
“…The growing tips of the regenerating axons have an appearance that is markedly different from the growth cones of embryonic neurons during development or in tissue culture. In contrast to that of embryonic neurons, the "growth cones" of regenerating lamprey reticulospinal axons lack filopodia and lamellipodia (Lurie et al, 1994), contain little F-actin (Jacobs et al, 1997), and elongate much more slowly Selzer, 1983, 1984;Lurie and Selzer, 1991). Ultrastructurally the growth cones are densely packed with neurofilaments (NFs) (Lurie et al, 1994), which suggested the hypothesis that assembly and transport of NFs into the growing tip might generate a protrusive force that contributes to regeneration.…”
mentioning
confidence: 99%